Flame retardant polyphosphoester copolymers as solid polymer electrolyte for lithium batteries. Issue 23 (25th May 2021) - Olmedo-Martínez, Jorge L.; Meabe, Leire; Riva, Raphaël; Guzmán-González, Gregorio; Porcarelli, Luca; Forsyth, Maria; Mugica, Agurtzane; Calafel, Itxaso; Müller, Alejando J.; Lecomte, Philippe; Jérôme, Christine; Mecerreyes, David
Abstract : Solid-state lithium batteries are considered one of the most promising battery systems due to their high volumetric energy density, in this work a flame retarded polymer electrolyte is proposed. Abstract : Solid-state lithium batteries are considered one of the most promising battery systems due to their high volumetric energy density and safety. Poly(ethylene oxide) (PEO) is the most commonly used solid polymer electrolyte in solid-state batteries. In this article, we introduce new polyphosphoester polymer electrolytes, which show improved flame retardant properties in comparison with PEO. For this purpose, new polyphosphoester copolymers were synthesized, including phosphoester, poly(ethylene glycol) (PEG) and UV cross-linkable vinyl units. Solid polymer electrolyte films based on polyphosphoester copolymers and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were prepared by curing under UV-light. The crystallinity present in the copolymers due to the PEG segment decreases with the amount of salt in the electrolyte, as seen by DSC. Solid polymer electrolytes based on polyphosphoester copolymers show ionic conductivity values as high as 2 × 10 −4 S cm −1 at 70 °C. FTIR analysis showed that lithium cations complexed with phosphoester groups provoked an increase in the lithium transference number to 0.26 as compared to that of PEO 0.17. Pyrolysis flow combustion calorimetry (PCFC) or micro-calorimetry results demonstrated the improved flame retardancy of the polyphosphoesters in comparison to a reference PEO based polymer electrolyte. The selected polyphosphoester solid electrolyte was investigated in a solid-state lithium cell Li 0 /polymer electrolyte/LFP battery showing a specific capacity retention close to 80% and coulombic efficiency greater than 98% over 100 cycles at 70 °C.